PERANCANGAN INTERIOR GRIYA GERABAH MELIKAN BAYAT DI KLATEN - Syaiful Anwar; Joko Budiwiyanto (Pendhapa, 2018)
ABSTRACTThe Griya Earthenware Planning aims to be an alternative educational or educational destination. Offering tourism options that provide pleasure through knowledge and experience about Melikan Village pottery products and their environment. The creative process in this work uses several approaches, namely the function approach, ergonomics and themes or styles. Approach function to find out the functions and benefits of Griya Gerabah for tourists or visitors and surrounding communities. The ergonomics approach is needed to know the human dimension and all things related to the five human senses that are related to the comfort and safety of visitors. Approach to the theme or style, which is used to support the identity of Gerya Gerabah as a pottery craft tourist attraction. The theme or style used is rustic, which is applied by applying to interior elements, namely floors, walls, ceilings, space filler elements, and space conditioning. The results of this work process are to create interior shapes and displays on Griya Gerabah that can support the activities of visitors or tourists at the Melikan Bayat Pottery Griya in Klaten and display designs with strong pottery characters.Keywords: Pottery, tourism, creative process, interior design